Adolescência: um olhar psicanalítico - Balduino, Giovanna Tiemy (Universidade Federal de São Carlos, 2022)
This undergraduate final paper has as main objective to explain the characteristic behaviors of the adolescence phase, aiming to understand why they happen and what their origin is. Therefore, we will approach the theme according to some of Sigmund Freud’s psychoanalytic concepts with the objective of clarifying this phase of psychosocial and sexual development, from birth, through the Oedipus complex and its revalidation at puberty. The text also explores a point of view elaborated by Anna Freud about the defense mechanisms used by adolescents when dealing with the abandonment of their parents' love.
Adolescence: a psychoanalytic view
Keywords: Adolescência; Puberdade; Sexualidade infantil; Complexo de Édipo; Psicanálise; Adolescence; Puberty; Child sexuality; Oedipus complex; Psychoanalysis; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA